Research on Unmanned End-effector and Its Buffer Parameters. Issue 5 (April 2021) - Zeng, Zhe; Shi, WenBo; Hou, YangYang; Hong, HuaJie
Abstract: Based on the future application of integrated reconnaissance and strike of small unmanned combat platform, the parameters of terminal strike weapon and terminal buffer mechanism are designed and analyzed in this paper. Firstly, the internal ballistic simulation of the terminal strike load is carried out and verified with the experimental results. Then, the buffering system is modeled, the buffering parameters are analyzed theoretically and the local optimal solution is analyzed, the general law of the local optimal solution is obtained, and the optimal solution is obtained. Finally, the simulation is carried out.